Co-creation Pathways to Inform Shared Governance of Urban Living Labs in Practice: Lessons From Three European Projects - Mahmoud, Israa Hanafi; Morello, Eugenio; Ludlow, David; Salvia, Giuseppe (Frontiers in Sustainable Cities, 2021)
Over recent decades Urban Living Labs (ULLs) have become a common space for co-creation processes’ experimentation, whereby new approaches for sustainable urban development are highly connected to support evidence-based policy generation. Europe seems a particular 'hotspot' for this approach whenever it comes to public policy and specifically planning for urban transition. Systemic changes related to urban governance and different public participatory mechanisms, as in the case of ULLs, demand a growing interest from the stakeholders and deliberation in decision-making mechanisms. In this research paper, we analyze co-creation pathways and different shared governance mechanisms in three ongoing European projects: CLEVER Cities, Sharing Cities, and SUNEX projects from a practice perspective. This comparative study investigates stakeholder engagement 1) scales, 2) mechanisms, 3) methodologies of engagement, and finally the co-creation pathway challenges and pitfalls. From the analyzed ULLs’ experiences, we identified key principles that suggest relevant clues to enable the consolidation of a forthcoming ULL 2.0 model and related innovation pathways for co-creating urban planning policies. We lastly reflect on the enablers and catalysts of co-creation processes to inform shared urban governance as major takeaways from our research.